Implementation preventive program for diabetic mellitus (PROLANIS) at Community Health Center in Indonesia: A qualitative study - Kadek Ida Krisnadewi,, Susi Ari Kristina, Tri Murti Andayani, Dwi Endarti (Journal of Applied Pharmaceutical Science, 2024)
Chronic diseases pose a significant challenge for elderly communities, with diabetes mellitus demanding particular attention. To address this, Indonesia’s Universal Health Coverage Program, commonly known as BPJS (Badan Penyelenggara Jaminan Sosial), established PROLANIS (Program untuk Lansia dan Penyakit Kronis). This program caters specifically to the elderly, offering comprehensive support through medical consultations, group education sessions, physical activities, SMS reminders, home visits, and regular health monitoring. However, PROLANIS implementation varies across regions. Geographical factors, access to facilities, stakeholder perspectives, and healthcare worker input all influence how the program is delivered. This research aims to identify the implementation of PROLANIS activities in five diverse regions in Indonesia. Utilizing a qualitative approach, the research employs in-depth interviews as its primary data collection method. The Consolidated Framework for Implementation Research (CFIR) guides the study, focusing on both intervention characteristics and the implementation process itself. PROLANIS services are integrated within existing healthcare structures at the village/sub-district level, seamlessly blending with other services available to the elderly population. Planning and execution of general activities adhere to national operational standards, ensuring consistency across regions. Physical exercise sessions, for instance, occur routinely, at least every 2 weeks or once a month. Recognizing regional differences, the program allows for special adaptations to overcome challenges. These adaptations, often influenced by human resource limitations, local infrastructure, and logistical hurdles such as transportation or scheduling constraints, ensure program effectiveness despite varying contexts.
Keywords: Prevention, implementation, community health Center, diabetic mellitus, Indonesia